Analysis of Light Grip Influence on Standing Posture. - Bellicha, Angélina; Trujillo-León, Andrés; Vérité, Fabien; Bachta, Wael (MDPI, 2021)
Upright posture control and gait are essential for achieving autonomous daily living activities. Postural control of upright posture relies, among others, on the integration of various sensory information. In this context, light touch (LT) and light grip (LG) of a stationary object provide an additional haptic sensory input that helps to reduce postural sway. When LG was studied through the grasp of a cane, the sensory role of this assistive tool was often limited to a mediation interface. Its role was restricted to transmit the interaction forces between its tip and the ground to the hand. While most studies involve participants standing in an unstable way, such as the tandem stance, in this paper we study LG from a different perspective. We attached a handle of a cane firmly to a stationary support. Thus, we can focus on the role of the hand receptors in the LG mechanism. LG condition was ensured through the tactile information gathered by FSR sensors placed on the handle surface. Moreover, participants involved in our study stood in a usual way. The study involved twelve participants in an experiment composed of two conditions: standing relaxed while lightly gripping an equipped handle attached to the ground, and standing in the same way without gripping the handle. Spatial and frequency analyses confirmed the results reported in the literature with other approaches.
Keywords: Servicios de salud; Biomecánica; Biosensores; Postural control; Light grip; Light touch; Healthcare; Force sensors